URGENSI EVENT IMAGE DAN TOURISM EXPERIENCE DALAM MENCIPTAKAN REVISIT INTENTION PADA DESA WISATA KABUPATEN SUMENEP - Yulistira, Silvia Rahma; A. S., Fathor (Universitas Nusa Cendana, 2024)
This research was motivated by a decrease in the number of visitors to the Kedatim Mangrove Tourism, Sumenep Regency. This research aims to determine the influence of event image and tourism experience on the intention to visit again, both directly and through the intervening variable of tourism satisfaction at Kedatim Mangrove Tourism. The sampling technique used was purposive sampling with a total sample of 100 visitors. The data collection technique was carried out by distributing questionnaires to respondents. The data analysis technique used is Partial Least Square. The research results show that event image (X1) does not have a significant effect on intention to revisit. Tourist experience (X2) has a significant effect on the intention to visit again. The image of the event (X1) has a significant effect on tourism satisfaction. Tourist experience (X2) has a significant effect on tourist satisfaction. Tourist satisfaction (Z) does not affect interest in returning to visit. Event image (X1) has no significant effect on the intention to revisit through tourism statistics. Tourist experience (X2) does not have a significant effect on the intention to visit again through tourism satisfaction. Keywords: Event Image; Tourism Experience; Tourism Statisfaction; Revisit Intention